Új Duna-menti Föderáció? : A DCCA mint Köztes-Európa integrációjának fejlesztője a 21. század hajnalán - Zachar, Péter Krisztián (Közép-Európai Közlemények, 2015)
The Danube Chambers of Commerce Association (DCCA) is the youngest international organisation in the Danube Region. The purpose of the DCCA is to develop sustainable competitiveness of the economies connected by the Danube. Members of the organisation are the economic chambers of Central-Europe. In this study the author is focusing on the importance of the new Danube-cooperation between the chambers of industry and commerce of Germany, Austria, Hungary, Serbia, Croatia, Romania and Bulgaria. The author tries to answer the question, how the economic cooperation can contribute to the development of the Danube region. The current study gives an insight into the strategy, work-plan, achievements and future plans of the DCCA. Established in 2010 the DCCA encourages cooperation and wants to enforce the advocacy of the enterprises operating and entrepreneurs living in the Danube basin. The cooperating economic chambers want to create a single platform of economic opportunities and to enhance economic cooperation in the Danube macro-region especially to further developement. The main questions of the DCCA touch the cooperation between old and new EU-members and non-member states, the promotion of regional and cross-border cooperation for further economic growth.